study on the Uropathogens in the Area of Sirt - Noful; Baiu, Y . M; S.H (Scientific Journal of University of Benghazi, 2026)
A thousand Mid-stream urine samples were collected from patients having urinary tract infections visiting Ibn-Sina Hospital in the city of Sirt in the time between March 2003 to September 2003. It has been found that more females than males were infected. The percentage of occurrence of UTI in females and males were 14.9%, and 4.7%, respectively. Urinary tract infections were found to be high in females aged between 15 and 40 years. Gram-negative bacteria were the main cause of these urinary tract infections, since it represented 81% of the total number of the bacterial infections, Escherichia coli caused 47%, or the highest percentage of all Gram-negative bacteria. Klebsiella spp. were the next bacterial group with 16%. While Enterobacter spp, Proteus mirabilis, Serratia spp. and Pseudomonas spp. came in the third place. Candida albicans (Fungus) represented about 11% and Gram-positive bacteria about 7% of the total number of infections.